Symboliczne aspekty wykorzystania ognia w późnośredniowiecznej i wczesnonowożytnej przestrzeni rodziny polskiej = Symbolic aspects of using a fire in late medieval and early modern Polish family space - Rogińska, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an attempt to reconstruct a symbolic significance of the fire in life of polish family between XIII and XVIII centuries. On the basis of analyze of rich ceremonialism, which can be found in home, household and church space, some types of this element were defined by way of example. The basic merit of a fire is its consumer value, which providing family with life was the base of assessment and creating of additional sense.
Keywords: rodzina - Polska; symbol; ogień; Polska - 13-18 w.